Respons Pertumbuhan Bibit Salak (Salacca edulis L.) terhadap Dosis Spora Endomikoriza pada Media Pembawa Pasir Vulkanik dan Pasir Laut - DEWA AYU ARI FEBRIYANTI; I WAYAN WIRAATMAJA; I KETUT SUADA (Agrotrop : Journal on Agriculture Science, 2020)
Response of Salak Seedling (Salacca edulis L.) Growth to Endomycorrhizal Spore Doses on Volcanic Sand and Sea Sand Carrier. Endomycorrhizae has several benefits, such as increase water absorption and nutrients of plant, protect plants from root pathogens and toxic substances, play a role in improving soil structure, and increase nutrient solubility. This study aimed to determine the growth response of salak seedlings to doses of endomycorrhizal spores in media carrying volcanic sand and sea sand. This study used a factorial randomized block design (RBD) with two treatments i.e. the number of spores and the type of carriers media. The results showed no significant interaction between the number of mycorrhizal spores doses with the carrier media on all observed variables. Spores doses significantly affected stem diameter and root mycorrhizal infection variables. The highest stem diameter was achieved at the dose of 75 spores that was 1.60 cm which was significantly different from control (1.28 cm), whereas the highest root infection was obtained at the dose of 225 spores (92.50%) which significantly higher than control (36.25%). At the observation of 4 MAP (month after planting) the highest root infection was obtained at the dose of 150 spores (82.50%) compared to control (10.00%). Volcanic sand carrier media produced the highest plant dry weight (3.59 g) which was significantly different to the sea sand (2.43 g).